Infiltration processes in cohesionless soils. Issue 2 (6th August 2012) - Schaufler, A.; Becker, C.; Steeb, H.; Diebels, Stefan
Abstract In this paper, a thermodynamically consistent four‐phase continuum model in the framework of the mixture theory is presented describing infiltration processes of suspensions in cohesionless granular material. The paper focuses on the distinct form of the constitutive relation for the volume production term of the fluidized particles and its consequences on the infiltration process. To this end a constitutive equation describing infiltration phenomena is proposed which includes only one material parameter. Therefore we study numerically a boundary value problem, which is characterized by a homogeneous field of the hydraulic gradient in the reference configuration at the time t0 = 0. Infiltration is affecting the distribution of the hydraulic properties and illustrates the consequences of the proposed constitutive equation for specific parameter choices. Furthermore it is shown how the material parameter can be estimated without explicit numerical calculations.